Relevansi Keshalehan Orang Tua dengan Kegemilangan Generasi Perspektif Al-Qur’an (Studi terhadap Surah Al-Kahfi Ayat 82) - Hidayatullah Ismail; Surbakti Amin; Dasman Yahya Ma’ali; Mochammad Novendri S (AL-FIKRA, 2022)
The glory of a generation is inseparable from what is composed and built by the parents, one of the most influential is the piety of the parents. This article deals with how the relevance of parental piety to the glory of the child in the study of surah al-Kahfi verse 82. This paper uses a thematic tafsir approach with several sources and references. As for the discussion, it is mentioned that among the parents as a good example and character shaper starting from the selection of a partner must be the aspect that is assessed is the piety of the prospective father or mother of the children later. Then maintain a good relationship with his god and teach the family in knowing God and religion. The power of parental prayer is an no less important aspect that parents must do. Then love and tenderness, in surah al-Kahfi verse 82 it is seen that a pious grandfather has thought of his grandchildren and descendants to become a glorious generation. Next is to pay attention to alimony from halal or haram sources to the family. Also give a good name to the child as in surah al-Kahfi the child is named by his parents with Sharim which means firm and sharp reflects the character of wise yet intelligent and Ashram which means holy place.